Manajemen Perawatan Masjid Baitul Hakam Pelindo III Perak Surabaya - Shobikhul Qisom; Wahyu Firman Ekasila; Fathurrahman Masrukan (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2019)
ABSTRACTBaitul Hakam Pelindo III mosque is an asset of a Pelindo Company, the management of maintainance of this mosque, including the the maintenance of the park with its cleanliness, the cleanliness of wudhu area, toilet and the cleanliness of the main area of the mosque. The process of maintaining activities are written in SOP, however the official are divided into two devisions, namely: internal and external official. The external official is the cleaning servicer from BSI, so the cleanliness of the mosque could be mainly devided into two, from the mosque and BSI. The aims of this research are to explain the management of maintenance of Hakam Pelindo III Surabaya mosque,  explain and give data about facilities are in Baitul Hakam mosque and inform the budget of maintanance  Baitul Hakam. The method of this research is qualitative with descriptive approach. The results of this research on the management of maintance Baitul Hakam mosque are to : explain the management of maintance if Baitul Hakam from management approach generally and explain the activities of  maintaining abaitul Hakam, the explain the various facilities and its maintance. The final is to explain the sum of budget that is used for maintaining Baitul Hakam Pelindo mosque.ABSTRAKMasjid Baitul Hakam Pelindo III Surabaya adalah aset dari perusahaan Pelindo III Surabaya, manajemen perawatan di masjid ini meliputi perawatan taman beserta kebersihannya, kebersihan tempat wudhu dan toilet dan kebersihan ruang utama masjid aktivitas perawatan tertulis dalam Standard Operating Procedure (SOP) namun pegawai masjid terbagi dua yaitu dari pegawai internal dan pegawai eksternal, pegawai eksternal masjid yaitu cleaning servis dari BSI (Best Servis Indonesia) karena itu SOP kebersihan terbagi menjadi dua juga dari masjid dan dari BSI. Tujuan dari penelitian ini adalah dapat memaparkan manajemen perawatan masjid Baitul Hakam Pelindo III Surabaya, menjelaskan dan memberi data fasilitas yang ada di masjid Baitul Hakam dan menginformasikan anggaran perawatan masjid Baitul Hakam. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Hasil penelitian manajemen perawatan masjid Baitul Hakam adalah menjelaskan manajemen perawatan masjid Baitul Hakam dari  sisi manajemen secara umum dan menjelaskan aktivitas perawatan di masjid Baitul Hakam surabaya, kemudian menjelaskan ragam fasilitas serta pengelolaannya terakhir menjelaskan total anggaran yang dikeluarkan masjid dari perawatan tersebut.